Classifying Job Value Profiles and Employment Outcomes Among Culinary Arts Graduates - Tae-Kyun Na; Saem Han (Societies)
The job values of college graduates are rapidly changing, but a mismatch between industry expectations and young chefs’ values has emerged. To capture the heterogeneity in job values that traditional variable-centered approaches may overlook, this study employed Latent Profile Analysis, a person-centered method, to classify the job value profiles of culinary arts graduates and examine their impact on major–job match and subjective well-being. A total of 386 culinary arts graduates, extracted from the Graduates Occupational Mobility Survey, were classified into six latent profiles. First, the most prevalent profile (Profile 4) emphasized environmental and developmental values, and was associated with a higher proportion of women and a greater likelihood of unemployment. Second, graduates who valued job attributes across all dimensions (Profile 1) were more likely to secure employment in or outside their field than those in Profiles 2, 3, and 5 were. Third, negative emotions increased the likelihood of belonging to Profiles 2, 3, and 5 compared to Profile 1. Finally, higher life satisfaction reduced the probability of belonging to Profiles 4, 5, or 6 compared to Profile 1. These findings emphasize the importance of aligning HR policies with graduates’ job values. Such alignment can enhance employment within graduates’ academic disciplines and improve their subjective well-being.